Economic uncertainty shocks and China's commodity futures returns: A time-varying perspective. (March 2021) - Lyu, Yongjian; Yi, Heling; Hu, Yingyi; Yang, Mo
Abstract: This paper is the first to analyse the impact of economic policy uncertainty (EPU) shocks on China's commodity futures returns using a time-varying parameter vector autoregressive framework. We both get similar conclusions from the literature, such as the negative effects of EPU shocks on commodity futures returns, and find new and intriguing results. First, the effects of EPU shocks on China's aggregate commodity futures returns vary over time and tend to be countercyclical; for example, the effects are stronger during the 2007–2009 global financial crisis. Second, there is significant heterogeneity in the reactions of different sectoral commodity futures returns to EPU shocks. We find that EPU shocks have a weaker effect on grains than on other commodities. Third, the reactions of aggregate commodity futures returns to different types of policy uncertainty shocks differ, with money policy uncertainty shocks producing relatively large effects. Fourth, compared with the traditional China EPU index proposed by Baker et al. (2016), the structural shocks to economic uncertainty measured by the new China EPU index generate larger and more significant effects on commodity futures returns. Highlights: Effect of China's EPU shocks on futures markets is time-varying and countercyclical. Compared with other market, grain market is relative less sensitive to EPU shocks. MPU shocks produces more significant effects than other policy uncertainty shocks. The new EPU shocks generate more significant effects than the traditional EPU index.